Ekosistem Kewirausahaan Pertanian: Pendekatan Kolaboratif Sebagai Pemicu Keberhasilan Bisnis Pertanian - Mukti, Gema Wibawa; Charina, Anne; Kusumo, Rani Andriani Budi (Universitas Galuh, 2026)
This paper aims to identify the actors and factors that create a successful agricultural entrepreneurship ecosystem. Agricultural development can run sustainably if the actors in it synergize with each other, giving the best contribution to create a successful agriculture. To achieve the research objectives, the researcher has conducted a literature analysis on collaboration between actors contained in the agricultural entrepreneurship ecosystem, so as to encourage agricultural activities to become more advanced and sustainable. In addition, this research also presents a model that shows an effective agricultural entrepreneurship ecosystem. Collaboration is an effort to increase the business and innovation capacity of each actor in the agricultural entrepreneurship ecosystem. This is an agricultural need for supportive policies, so as to encourage technological innovation and information/knowledge transfer among agricultural actors (farmers, government, agribusiness companies, financial institutions, social communities). This condition is expected to encourage the progress of agriculture as a whole, involving all actors involved in it.